2018
DOI: 10.3390/nu10040423
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training Prevents Muscle Loss Induced by Caloric Restriction in Obese Elderly Individuals: A Systematic Review and Meta-Analysis

Abstract: It remains unclear as to what extent resistance training (RT) can attenuate muscle loss during caloric restriction (CR) interventions in humans. The objective here is to address if RT could attenuate muscle loss induced by CR in obese elderly individuals, through summarized effects of previous studies. Databases MEDLINE, Embase and Web of Science were used to perform a systematic search between July and August 2017. Were included in the review randomized clinical trials (RCT) comparing the effects of CR with (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 48 publications
3
57
0
7
Order By: Relevance
“…Nevertheless, the intervention will provoke a reduction in BF compensated by an increase in FFM. [18] Among the mechanisms that would explain the scant difference in weight loss between people following a diet or a diet/PA combination, other authors suggest that; 1) this is based on the patients increasing adaptation to the physical activity program, which implies a lower energy expenditure over the time [19]; and 2) that there is an increase in appetite as the energy expenditure is increases due to PA [20].…”
mentioning
confidence: 99%
“…Nevertheless, the intervention will provoke a reduction in BF compensated by an increase in FFM. [18] Among the mechanisms that would explain the scant difference in weight loss between people following a diet or a diet/PA combination, other authors suggest that; 1) this is based on the patients increasing adaptation to the physical activity program, which implies a lower energy expenditure over the time [19]; and 2) that there is an increase in appetite as the energy expenditure is increases due to PA [20].…”
mentioning
confidence: 99%
“…Moreover, CR in monkeys reduces morbidity and mortality for cancer, cardiovascular disease and frailty 39,40 . Indeed, in contrast to the scientifically unsupported opinion that long-term CR promotes frailty [41][42][43] , recent data from the Wisconsin CR Primate study clearly show that the levels of weakness, poor endurance, slowness, low physical activity and frailty were significantly lower in the CR than in the ad-libitum fed monkeys 44 .…”
Section: Calorie Restrictionmentioning
confidence: 82%
“…Furthermore weight loss via cr is accompanied by a significant decrease in lean body mass (lbm) 41 A loss of muscle mass is also associated with frailty and increased mortality at advanced ages, and is a challenge for successful aging 42 However a meta-analysis reviewing factors of exercise, training, aging, sarcopenia, muscle mass, strength training, caloric restriction diets concluded that crrt (cr with resistance training) is able to prevent almost 100% of cr-induced muscle loss, while resulting in fbm and bm reductions that do not significantly differ from cr. 43 Effects of cr on agerelated impairments in wound healing in rodents have been variable, 20,21,22 In general, restricted animals have not demonstrated improvements in wound healing and in some cases even appear to be more impaired than age-matched, ad libitumfed, senescent counterparts 21 [reiser et al, 1995]. However, at least one report has suggested that if restricted animals are re-fed ad libitum before wounding, healing rates improve markedly and are superior to those in non restricted controls 22 [reed et al, 1996].…”
Section: 40mentioning
confidence: 99%